Nexus between Economic Policy Uncertainty and Bank Liquidity Creation: Moderating Role of Bank Regulations and Credit Risk - Saha, Sabuj; Sen, Kanon Kumar; Bishwas, Prodip Chandra (Finance & Economics Review, 2024)
Purpose: This paper analyzes the effects of economic policy uncertainty (EPU), bank regulations, and credit risk on the asset and liability sides of liquidity creation in developed and developing countries. Methods: The sample comprises 100 companies in developed and developing countries from 2015 to 2021. We used a dynamic Generalized Method of Moments (GMM) estimator to test the hypothesis. We also performed the Sargan test of over-identification or J-statistics to check the validity of instruments in the GMM model. Additionally, we conducted a robustness test on our analysis based on average assets and average capital. Results: We find that Economic Policy Uncertainty (EPU) significantly negatively impacts asset-side liquidity creation in developed and developing countries. However, EPU significantly positively impacts liability-side liquidity creation only in developed countries. Interestingly, higher credit risk can effectively counteract the adverse effects of EPU on asset-side liquidity creation and encourage a positive impact on liability-side liquidity creation in developed and developing countries. Moreover, stricter bank regulations, including activity restriction and capital stringency, can weaken the negative effects of EPU on asset-side liquidity creation in developed and developing countries. However, we do not find any significant effect of higher bank regulations on the relationship between liability-side liquidity creation and EPU. Implications: Since financial institutions can make riskier decisions to keep their businesses going in an uncertain economy, regulators need to act in advance to restore confidence in credit growth and financial resilience. The government should assess the short-term and long-term consequences of any policy implications. Originality: While most studies concentrate on total liquidity creation from a cross-country perspective, our study provides new evidence by breaking down liquidity creation into asset-side and liability-side liquidity creation and examining the research separately in developed and developing countries.